The numerical simulation and wellbore modelling of steam injection and stored heat recovery from light oil reservoir. Issue 1 (2nd January 2021) - Zafar, Atif; Su, Yuliang; Li, Lei; Mehmood, Asif; Wang, Han; Fu, Jingang
ABSTRACT: Steam injection and thermal recovery of oil from the reservoir are increasing day by day. However, the recovery of the heat remained stored in the steam-flooded oil reservoir is nor in practice neither researched previously. A novel concept of steam injection and energy recovery from a light oil reservoir is presented in this paper. Reservoir numerical model of an actual oil field was generated and simulated with steam injection. Different parameters of thermal properties of geologic formations were discussed and adopted as per actual geology of the study area for more realistic simulation of heat storage, dissipation, and losses. After the optimum oil recovery, water was circulated through the same injection well into the reservoir to extract the energy in the form of heat, stored during the steam injection phase. The effects of different completion schemes of injection well were also simulated, discussed and pointed out for optimum oil recovery. Oil recovery factor is the most important parameter from both research and field development point of views. The comparative analysis was also carried out with the oil production without steam injection and found that steam flooding increased oil recovery factor up to more than 15% by decreasing the production time period up to 40% as compared to without steam injection oil production. The transmission of heat through conduction and convection mechanisms in the porous media, and through advective, dispersive and diffusive processes in the fluid was modeled. To fully investigate the feasibility of the concept presented in this paper, the production wellbore modeling was also carried out and temperature profile of recovered heat energy at the wellhead was obtained by acknowledging the thermal losses and found to be very useful for any direct and indirect utilization of heat throughout the energy recovery period of the reservoir.